Chemical, biochemical, and fatty acids composition of seeds of Opuntia boldinghii Britton et Rose - García Pantaleón, D.M.; Flores Ortiz, M.; Moreno Álvarez, M.J.; Belén Camacho, D.R.; Medina Martínez, C.A.; Ojeda Escalona, C.E.; Padrón Pereira, C.A. (Journal of the Professional Association for Cactus Development, 2009)
Opuntia boldinghii Britton and Rose, is a Cactaceae distributed in Venezuelan semiarid and coastal regions. In this research, the proximate composition showed: moisture 7.66%; ethereal extract 5.53 g/100g; protein (N x 6.25) 2.89 g/100g; total ash 2.53 g/100g; crude fiber 16.26 g/100g. Minerals determined were: calcium 0.59 mg/100g; phosphorus 24.93 mg/100g; potassium 2.80 mg/100g; iron 1.34 mg/100g. Total carotenoids value was 0.92 mg/100 and vitamin C concentration was 4.15 mg ascorbic acid/100g. Caloric value was calculated at 349.07 Kcal. Antinutritional factors present were: total tannins 0.33%; condensed tannins 0.08% of leucocyanidin equivalent; trypsin inhibitors units 25.26 mg pure inhibited trypsin/g and non-detected saponins. Fatty acids profile showed: linoleic 67.20%; oleic 18.00%; palmitic 10.40%; stearic 3.00%; palmitoleic 0.50%. In vitro protein digestibility was 28.15%. In conclusion, O. boldinghii seeds are an important source of natural fiber and, given its high linoleic acid content, its oils can be used as a nutraceutic agent.